Comparison of two different methods for CA19-9 antigen determination - Deinzer, Martina; Faißner, Ralf; Metzger, Tobias; Kaminski, Wolfgang E.; Löhr, J.-Matthias; Neumaier, Michael; Brinkmann, Thomas (Clinical laboratory, 2010)
BACKGROUND: This study was designed to investigate the clinical performance of the Access GI Monitor (Beckman Coulter) on the UniCel DxI 800, a method for CA19-9 antigen determination, and to compare with CA19-9 assay on the AxSYM system (Abbott). - METHODS: 1,063 serum samples from unselected patients with different underlying diagnoses were tested with both methods. Passing-Bablok regression analysis and Bland Altman analysis was performed. In addition, using ROC analysis, the distribution of Access GI Monitor and AxSYM CA19-9 antigen levels was tested in patients with pancreatic cancer (n = 50), acute inflammatory disease (n = 20), and with chronic inflammation of the pancreatic gland (n = 18). Furthermore, four patients with pancreatic cancer were monitored individually in their courses of the disease (before, during, and after therapeutic procedures) to compare their CA19-9 values with regard to inter-method concordance. - RESULTS: Passing-Bablok analysis showed a systematic difference with R = 0.93, slope 0.75, and intercept -1.0. Bland Altman analysis showed a wide scatter of relative differences between both methods, especially in the low end measuring range. In the selected group of patients with pancreatic diseases the analysis of concordance revealed 95.5 % agreement between both methods with a comparable area under the ROC curves (0.73 vs. 0.76). A clear concordance was found for all four selected patients. - CONCLUSIONS: Although we found significant systematic measuring variations in the global analysis, the two different automated methods for the quantitative determination of CA19-9 antigen were comparable with respect to their clinical accuracy and applicability to support decision making in the management of pancreatic cancer.
Matthias Löhr ist in der Verfasserangabe fälschlich als "Mathias Löhr" geschrieben
Kein DOI vorhanden
Gesehen am 27.10.2023